The Question of Choice in an Achievement (Language Circle: Journal of Language and Literature, 2019)
Achievement tests administered at national level play a significant role in the lives of test-takers as well as the whole society. This paper aims to investigate the effect of giving students a choice between two optional questions on their overall performance in a high-stake achievement test for university admission. It is hypothesized that questions targeting writing-based productive skills and language system necessitate display of abilities which are different from fact-based questions designed around story content. The two items are assumed to reflect different constructs that require different criteria of assessment. Consequently, the student’s overall score is affected by the item they choose to answer, which might not be reflective of their real language abilities. An open-ended interview was carried out with ten teachers working with grade 3 students in model secondary schools to investigate the nature of the two types of test items and their impact on the student’s performance. The data has proved that giving choice in an achievement test generates different performances that are assessed differently. It is recommended that in order to address the question of fairness, it is important to clearly define and balance the construct of the items that affect the student’s choice and performance.